Investigation and Suppression of Oxygen Release by LiNi0.8Co0.1Mn0.1O2 Cathode under Overcharge Conditions. Issue 20 (10th April 2022) - Shi, Chen‐Guang; Peng, Xinxing; Dai, Peng; Xiao, Penghao; Zheng, Wei‐Chen; Li, Hong‐Yang; Li, Hang; Indris, Sylvio; Mangold, Stefan; Hong, Yu‐Hao; Luo, Chen‐Xu; Shen, Chong‐Heng; et al.
Abstract: The safety issue of lithium‐ion batteries is a crucial factor limiting their large‐scale application. Therefore, it is of practical significance to evaluate the impact of their overcharge behavior because of the severe levels of oxygen release of cathode materials during this process. Herein, by combining a variety of in situ techniques of spectroscopy and electron microscopy, this work studies the structural degradation of LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) accompanying the oxygen release in the overcharge process. It is observed that a small amount of O2 evolves from the initial surface at ≈4.7 V. When charging to a higher voltage (≈5.5 V), a large amount of O2 evolves on the newly formed surface due to the occurrence of microcracks. Based on experimental results and theoretical calculations, it is determined that the oxygen release mainly occurs in the near‐surface regions, where the remaining oxygen vacancies accumulate to create voids. To suppress the oxygen release, single‐crystalline NCM811 with integrated structure is introduced and serves as a cathode, which can effectively inhibit morphology destruction and reduce the activation of lattice oxygen in the surface region. These findings provide a theoretical basis and effective strategy for improving the safety performance of Ni‐rich cathode materials in practical applications. Abstract : Safety issues hinder the commercialization of Ni‐rich cathode materials. Oxygen release occurs from different regions during the overcharge process as shown by several in situ spectroscopy techniques and electron microscopy. O2 appears first in the near‐surface region of secondary particles, then on the fresh surface between primary particles due to the occurrence of microcracks. Single‐crystalline NCM811 with integrated structure could reduce this phenomenon.